Placebo Groups in Research on the Effectiveness of ABA Therapeutic Techniques - Bąbel, Przemysław; Bajcar, Elżbieta Anita; Marchewka, Katarzyna; Sikora, Katarzyna (Frontiers in Psychology, 2018)
Behaviour analysts have shown that a single-subject experimental design (SSED) is a useful tool for identifying the effectiveness of specific therapeutic techniques, whereas researchers outside applied behaviour analysis (ABA) maintain that randomised placebo-controlled trials (RPCT) provide the most definite test of efficacy. In this paper the possible benefits that could result from supporting SSED studies results by placebo control groups are discussed. However, the use of placebo groups in psychotherapy research arouses considerable controversy and many researchers argue against it. The main aim of this paper is to clarify theoretical and methodological problems associated with using placebo groups in psychotherapy research and to demonstrate that these problems can be solved if the assumptions on which they are based are reformulated. The article also discusses ethical issues about the use of placebo groups in research on the effectiveness of psychotherapy.